Implementasi Metode Jarimatika dalam Meningkatkan Kemampuan Berhitung pada Operasi Kabataku - Ajeng Sarjono; Elvia Anggi Ayu Septiani; Eka Noviya Muslichah; Nofi Triana Sari (Jurnal Syntax Admiration, 2023)
Jarimatics is a simple and fun way of teaching children basic computation according to the principle: start by correctly understanding first the concepts of numbers, number symbols, and basic counting operations, then teaching how to count with the fingers of the hand. The low ability and desire of students in counting on mathematical subjects makes the method of JARIMATIKA suitable introduced to students SDN 02 Pasar Keong as a solution in completion of mathematics as well as improving the ability to count on Operation KABATAKU. The method of implementation performed by the Community Devotion Team is divided into 3 sessions namely: 1) delivery of material about jarimatika method and Operation count using such method, 2) ice breaking in order to arouse the spirit of students during the activity, 3) Applying the material that has been given with the use of staircase snake tools. Thus the student's ability to calculate improved and better than before taught the Jarimatic Method and the student considered counting a pleasant thing.